SCIENTIFIC RESEARCH OF EFFECTIVE METHODS OF ENRICHMENT OF KAOLIN ORES - Хожиева Мухлиса Обид кизи; Юлдошева Шахрийона Жамолиддин кизи (Scholars Digest Publishing, 2025)
Kaolin ores, as high-quality aluminosilicate minerals, are widely used in various industries. The article is devoted to the analysis of the processes of enrichment of kaolin ores, mechanical, chemical, flotation and thermal methods are considered in detail. This study analyzes the effectiveness of each method, as well as technological, environmental and economic factors associated with their implementation. optimization of kaolin enrichment processes.
Keywords: Kaolin, ores, enrichment, flotation, chemical, mechanical, thermal, efficiency, ecology, industry.